Estimation of Non-Stationary Frequency and Fundamental Components for Power Electronics-Dominated Energy Systems - Peng Li; Hin Sang Lam; Boli Chen; Raymond Wai M. Ng; Thomas Parisini; S. Y. Hui (IEEE Open Journal of Power Electronics)
Estimation of fundamental frequency and sinusoidal components is required for the regulation of modern power electronics-dominated power systems. Most of the existing estimation methods are designed for signals with stationary frequency. Hence, their accuracy could significantly degrade in the face of non-stationary frequencies, which is common in low-inertia power systems. In this paper, we propose a novel scheme for real-time estimation of a time-varying power frequency and the resulting fundamental signal. This is a time-domain method for (1) estimating non-stationary frequency and (2) fundamental signal reconstruction. It has the advantage of tracking the fundamental frequency component and treating all harmonics and subharmonics as noise. The method is based on a kernel-based estimation scheme and characterized by high accuracy, fast response, and noise immunity because of the inclusion of non-asymptotic kernel functions. The effectiveness of the proposed estimation scheme for non-stationary frequency tracking and fundamental signal reconstruction is verified by simulation and experimental results, which explore the use of the proposed scheme for frequency extraction of power signals appear in real world low-inertia systems.